Restating Environmental Law - Hester, Tracy; Percival, Robert; Russell, Irma; Flatt, Victor; Mintz, Joel (Columbia Journal of Environmental Law, 2019)
Although environmental law springs from deep roots in centuries of common law, during the last forty years in particular it has grown into a well-established and important legal field in the United States with enormous practical consequences. Maturity, however, has also made it notoriously complex, and environmental law's overlapping statutory schemes and inconsistent federal and state programs have sparked recurring conflict, controversy, and criticism. This fractured and complicated network of environmental laws and programs has become increasingly difficult to modify or update to account for emerging environmental concerns. As a result, numerous experts, scholars, and advocacy groups have offered proposals to reform U.S. environmental laws, but these initiatives have failed to produce significant statutory advances or implementation. In fact, Congress has not enacted major new environmental legislation since its passage of the Clean Air Amendments of 1990, and existing federal environmental statutes have remained essentially unchanged for over twenty years. ... This article explores whether U.S. environmental law needs either a Restatement or other Project that would offer a comprehensive analysis, and it overviews possible reasons why the ALI has not previously undertaken such a Project. Second, we report on an ongoing effort by a workgroup of ALI members to define a potential environmental or natural resource law Project that might offer the best opportunity for clarification or reform. This workgroup of nearly fifty ALI members includes leading environmental practitioners and academics, and it has proposed two carefully defined and limited Projects in the environmental law area. If the ALI undertakes one of the more focused Projects suggested by the workgroup, however, the Institute would not foreclose its ability to develop a broader Principles of Environmental Law or a full Restatement in the future. Third, we assess arguments that any comprehensive analysis of environmental law by the ALI might do more harm than good because it would "freeze" environmental and natural resource law at a point where it still needs further fundamental reform. Finally, we discuss possible future steps to facilitate comprehensive work by the ALI on environmental issues.